The development of fire risk assessment method for heritage building - Ibrahim, Md. Najib; Abdul Hamid, Khirani; Ibrahim, Mohd Shariffuddin; Mohd Din, Azrin; Mohd Yunus, Rodzyah; Yahya, Mohamad Ridzuan (2011)
This paper examines the criteria and attributes for assessing fire risks in building. Using the Analytical Hierarchy Method (AHP) a survey questionnaire was developed based on the identified criteria and attributes of fire risks for heritage buildings in Malaysia. The survey questionnaire was administered to consultant, Fire Rescue Department (FRDM) personnel, maintenance professional and insurance professional. The data were analysed using ExperChoice2000 software. The result of the research is the weightage for each criterion and its respective attributes.